Politicizing Solidarity in Times of Crisis: The Politics of Alternative Action Organizations in Greece, Italy, and Spain. (May 2018) - Zamponi, Lorenzo; Bosi, Lorenzo
Alternative action organizations (AAOs) are collective bodies engaged in carrying out alternatives to dominant socioeconomic and cultural practices through actions that aim to provide people with alternative ways of enduring day-to-day difficulties and challenges in hard economic times. They are often interpreted as merely "philanthropic" actors, although it is not rare to see them go beyond the provision of direct services to people in need and end up pursuing political goals through political means. This article focuses on the process of politicization, that is, the transition of issues from the private to the public sphere and thus the use of public forms of contention (e.g., protest) proposing public solutions at the collective level instead of private solutions at the individual level. We argue for the role of the crisis in the politicization of AAOs. In particular, we show that the appropriation of the context as a context of economic crisis in the discourse of AAOs has a visible effect on their politicization, in terms of both repertoire of actions and goals. Furthermore, we show that social solidarity organizations, those that are not inherently politicized, are the main protagonists of this crisis-triggered transition. The article draws on statistical analysis of the data collected through the coding of AAOs' websites in Greece, Italy, and Spain.